2014
DOI: 10.1128/aac.03514-14
|View full text |Cite
|
Sign up to set email alerts
|

EnhancedIn VitroFormation and Antibiotic Resistance of Nonattached Pseudomonas aeruginosa Aggregates through Incorporation of Neutrophil Products

Abstract: e Pseudomonas aeruginosa is a major pathogen in cystic fibrosis (CF) lung disease. Children with CF are routinely exposed to P. aeruginosa from the natural environment, and by adulthood, 80% of patients are chronically infected. P. aeruginosa in the CF airway exhibits a unique biofilm-like structure, where it grows in small clusters or aggregates of bacteria in association with abundant polymers of neutrophil-derived components F-actin and DNA, among other components. These aggregates differ substantially in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 57 publications
1
36
0
Order By: Relevance
“…Bacteria form similar biofilm aggregates within high-density gels when bacterial motility is restricted, and conditions associated with CF sputum and chronic inflammation, including the presence of neutrophil elastase, DNA, and amino acids, are sufficient to promote biofilm aggregate formation (41,122,123). Importantly, this nonattached biofilm growth also confers resistance to antibiotics and neutrophil killing in vitro (41).…”
Section: Chronic Bacterial Lung Infections In Cystic Fibrosismentioning
confidence: 99%
“…Bacteria form similar biofilm aggregates within high-density gels when bacterial motility is restricted, and conditions associated with CF sputum and chronic inflammation, including the presence of neutrophil elastase, DNA, and amino acids, are sufficient to promote biofilm aggregate formation (41,122,123). Importantly, this nonattached biofilm growth also confers resistance to antibiotics and neutrophil killing in vitro (41).…”
Section: Chronic Bacterial Lung Infections In Cystic Fibrosismentioning
confidence: 99%
“…Concomitant use of the two agents is now common, but has not been tested prospectively. Several independent in vitro studies have reported antagonism between azithromycin and tobramycin against P. aeruginosa 46 . We have hypothesized that combined therapy with these two medications may unexpectedly provide less rather than more clinical improvement.…”
Section: Introductionmentioning
confidence: 99%
“…In chronic CF airways, P. aeruginosa does not form; however, these flat, thick biofilms covering the airway surface but reside instead in three-dimensional biofilms also called suspension biofilms or non-attached aggregates [212,213,214,215,216]. These bacterial aggregates accompanied by large amounts of PMNs represent the typical clinical image found in the airways of CF patients chronically infected with P. aeruginosa (Figure 1) [212,213,214,215,216]. …”
Section: Adaptation Of P Aeruginosa To Neutrophil-mediated Attackmentioning
confidence: 99%
“…ecDNA is a main component of P. aeruginosa aggregates, and ecDNA obtained from necrotic PMNs has been shown to support aggregate growth of P. aeruginosa [214]. NET formation can likely be the source of PMN DNA in CF airways, since P. aeruginosa elicits robust NET release in PMNs [122,128,170,205].…”
Section: Adaptation Of P Aeruginosa To Neutrophil-mediated Attackmentioning
confidence: 99%